2011
DOI: 10.1111/j.1469-1809.2011.00647.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification and In Silico Analysis of Novel von Hippel-Lindau (VHL) Gene Variants from a Large Population

Abstract: SummaryMutational inactivation of the VHL gene is the cause of von Hippel-Lindau (VHL) disease, an autosomal dominant hereditary cancer syndrome predisposing to haemangioblastomas, pheochromocytomas and clear-cell renal carcinomas. The gene product (pVHL) functions as an adapter in cellular processes including cell growth and apoptosis. VHL mutation analysis was carried out in 426 unrelated subjects with phenotypes ranging from VHL syndrome, to isolated VHL-related tumours that could represent the first manife… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 72 publications
0
18
0
Order By: Relevance
“…This contrasts with reports of other heterozygous VHL mutations encoding the same amino acid residue (VHL P138R, P138T) that have been reported in VHL syndrome and renal cancer. [24][25][26] We also show that this mutation is not only associated with elevated EPO levels but also with a hallmark of primary polycythemia (ie, EPO hypersensitivity).…”
Section: Discussionmentioning
confidence: 88%
“…This contrasts with reports of other heterozygous VHL mutations encoding the same amino acid residue (VHL P138R, P138T) that have been reported in VHL syndrome and renal cancer. [24][25][26] We also show that this mutation is not only associated with elevated EPO levels but also with a hallmark of primary polycythemia (ie, EPO hypersensitivity).…”
Section: Discussionmentioning
confidence: 88%
“…Fifteen articles from nine different countries (Chacon‐Camacho et al, ; Chen et al, ; Gergics et al, ; Gomy et al, ; Huang et al, ; Hwang et al, ; Leonardi, Martella, Tosatto, & Murgia, ; Levine, Collins, Horton, & Schimke, ; Prasad et al, ; Rasmussen et al, ; Ruiz‐Llorente et al, ; Vikkath et al, ; Wang et al, ; Wu et al, ; Zhang et al, ) reported a vHL cohort with at least one child/adolescent and a total of more than five patients (Table ). In total, 62 patients were identified with a vHL diagnosis before 18 years, and information about their ages, genotypes, and phenotypes were extracted from the articles when available.…”
Section: Resultsmentioning
confidence: 99%
“…Several research articles have mentioned its effectiveness in identifying the deleterious, disease related mutations, thus predicting the pathogenic phenotypic alleles in correlation to its functional and structural damaging properties (Carvalho et al, 2007(Carvalho et al, , 2009Goldgar et al, 2004;Karchin, 2009). Bioinformatics application in analyzing the possible pathogenic phenotype induced by the genetic variants in VHL (Leonardi et al, 2011) and in evaluating their molecular mechanisms involved in Type 2 diabetes mellitus (Sharma et al, 2005) has provided an important evidence for the effectiveness of a computational platform in determining the disease related alleles. The computational identification of damaging mutations in 77 cell cycle proteins (Savas et al, 2005), and pathogenic mutant prioritization in 45 cytokine proteins (Shen et al, 2006), have further proved the effectiveness of using computational algorithms in a very precise prediction of disease related SNPs (single nucleotide polymorphisms).…”
Section: Introductionmentioning
confidence: 99%